RUMPUT LAUT GRACILARIA SP. SEBAGAI FITOREMEDIAN BAHAN ORGANIK PERAIRAN TAMBAK BUDIDAYA - Komarawidjaja, Wage (Jurnal Teknologi Lingkungan, 2005)
Phytoremediation is the utilization of green plants to remove pollutants from the environment. A central component of this technology is the use of plants as living technologies that provide services in addressing environmental issues. Therefore, based on the hydrological understanding, phytoremediation technology can be used to manage nutrient and water dynamics; It can lead significant improvement in water quality as well as remediation of degraded ecosystem. Laboratory experiment result indicated, seagrass called Gracilaria sp. have the ability in reducing organic substance as total Nitrogen (N-Total) from 1,2 mg / L into 0.4 mg / L in less than 10 hour. The integration of seagrass into pond ecosystem as organic substances phytoremedian of exceeding fish-feed accumulation expected to become an alternative technology for water quality recovery enhancement.